Risk Management in Islamic Education Based on ISO 31000 and Maqasid al-Shariah - Anisyah Nur Aini; Siti Julaiha (Al-Qalam Institue, 2025)
Islamic educational institutions increasingly face academic, administrative, financial, and safety challenges that require formal risk management to ensure sustainability. This research aims to analyze how ISO 31000 can be integrated with Maqasid al-Shariah to construct a risk governance model that is both technically effective and ethically grounded. Using a library research methodology, relevant books, international journal articles, previous studies, and risk management documents were critically analyzed through content analysis to identify conceptual patterns and gaps. Findings reveal three major results: first, risk governance is implemented using dual filters technical feasibility and Sharia ethical compliance; second, ISO-driven mitigation supports institutional sustainability through strong documentation, audits, and follow-up actions; third, holistic risk mapping aligns risk priorities with the five Maqasid dimensions, ensuring that mitigation protects religion, life, intellect, progeny, and property. This study contributes a hybrid risk management framework that transcends procedural compliance by embedding Islamic ethical imperatives. It implies that the sustainability of Islamic education depends on institutionalizing continuous evaluation and value-based decision-making.